Transformasi Komunikasi Dinas Kominfo Kota Medan dalam Implementasi Smart City Berbasis Medan Dataku - Hanafi, Muhammad Reza; Kholil, Syukur (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study explores the transformation of organizational communication within the Department of Communication and Information (Kominfo) of Medan City in implementing the smart city program through the Medan Dataku platform. It addresses the core question: how does Kominfo adapt its communication strategies to overcome technological fragmentation and digital literacy gaps among civil servants? Using a qualitative case study approach, data were gathered through interviews, observations, and document analysis involving key actors across local government institutions. The findings reveal that despite advances in digital platforms, communication challenges persist due to unintegrated systems, resistance to change, and uneven digital capabilities. However, adaptive strategies such as inclusive communication practices, public dialogue through digital channels, and value-based messaging have strengthened public trust and interdepartmental collaboration. The study concludes that effective smart governance requires not only technological innovation but also ethically grounded and contextually sensitive communication systems.